Synthesis, anti-thymidine phosphorylase activity and molecular docking of 5-thioxo-[1,2,4]triazolo[1,5-a][1,3,5]triazin-7-ones - Bera, H.; Lee, M.; Sun, L.; Dolzhenko, Anton; Chui, W. (2013)
In our lead finding program, a series of 5-thioxo-[1,2,4]triazolo[1,5-a][1, 3,5]triazin-7-ones and their 5-thio-alkyl derivatives were designed and synthesized which contained different substituents at ortho-position of 2-phenyl ring attached to the fused ring structure. The preliminary pharmacological evaluation demonstrated that the synthesized compounds exhibited a varying degree of inhibitory activity towards thymidine phosphorylase (TP), comparable to reference compound, 7-Deazaxanthine (7-DX, 2) (IC50 value = 42.63 lM). The study also inferred that the ortho-substituted group at the phenyl ring and 5-thio-alkyl moiety imparted steric hindrance effects in the binding site of the enzyme, leading to a reduced inhibitory response. In addition, compound 3a was identified as a mixed-type inhibitor of TP. Moreover, computational docking study was performed to illustrate the important structural information on the plausible ligand-enzyme binding interactions. © 2013 Elsevier Inc. All rights reserved.